De 1907 à 1910 : (Bureau Socialiste International, 1910)
I: Grande Bretagne, II Allemagne, IVa Autriche, IVb Bohême, V Hongrie, VI France, VII Italie, VIII Espagne, X Russie, XIa Pologne, XIb Finlande, XII Norvège, XIII Suède, XIV Danemark, XX Serbie, XXI Bulgarie, XXVIII Etats-Unis.